2019
DOI: 10.1016/j.celrep.2019.02.054
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 Deubiquitination by USP21 Regulates Cell Cycle Progression and Paclitaxel Sensitivity in Basal-like Breast Cancer

Abstract: SUMMARYThe transcription factor FOXM1 contributes to cell cycle progression and is significantly upregulated in basal-like breast cancer (BLBC). Despite its importance in normal and cancer cell cycles, we lack a complete understanding of mechanisms that regulate FOXM1. We identified USP21 in an RNAi-based screen for deubiquitinases that control FOXM1 abundance. USP21 increases the stability of FOXM1, and USP21 binds and deubiquitinates FOXM1 in vivo and in vitro, indicating a direct enzyme-substrate relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 61 publications
4
65
1
1
Order By: Relevance
“…In addition, it has been shown that the FOXM1-PSMB4 axis can play a catalytic role in the proliferation and development of cervical cancer [28]. More surprisingly, FOXM1 plays a vital role in many other cancers [29][30][31][32]. In our study, FOXM1 was upregulated in tumor tissues compared to normal tissues, suggesting a signi cant correlation with melanoma.…”
Section: Discussionsupporting
confidence: 46%
“…In addition, it has been shown that the FOXM1-PSMB4 axis can play a catalytic role in the proliferation and development of cervical cancer [28]. More surprisingly, FOXM1 plays a vital role in many other cancers [29][30][31][32]. In our study, FOXM1 was upregulated in tumor tissues compared to normal tissues, suggesting a signi cant correlation with melanoma.…”
Section: Discussionsupporting
confidence: 46%
“…In KICH, genes related to the aspartate-malate shuttle were also upregulated suggesting that aspartate can act as an anaplerotic source for the TCA cycle. Further, FOXM1 and its targets (ASNS and FASN) were upregulated in RCC 37 . ASNS promotes the synthesis of asparagine, which is shown to be a suppressor of apoptosis in response to the glutamine withdrawal 38 .…”
Section: Discussionmentioning
confidence: 95%
“…FOXM1, a transcription factor that contributes to cell cycle progression, is significantly upregulated in BLBC. 54 In hepatocellular carcinoma, USP21 was found to promote tumor growth through stabilization of MEK2. 55 In hematologic malignancy, USP9X was shown to stabilize BCR-ABL and to promote BCR-ABL kinase signaling in CML.…”
Section: Figure 5 Ba Restores the Sensitivity Of K562r Cells To Im Tmentioning
confidence: 99%